Boards of directors, audit committees and financial reporting quality. A systematic review - Karolina Skorulska; Dorota Dobija (Zeszyty Teoretyczne Rachunkowości, 2016)
Measurement of financial reporting quality is a problematic task because financial reporting is difficult to observe and measure. The aim of the article is to present the methods of financial reporting quality meas-urement and a systematic review of literature on the effects of corporate governance reforms on the qualityof financial reporting. The main research questions are: (1) what are the possibilities of measuring financial reporting for research purposes, (2) which of the methods of measuring the quality of financial reporting are used in research on corporate governance, and (3) which variables used in measuring corporate gov-ernance factors affect financial reporting quality? To answer these questions, a critical analysis of literature and a systematic review of research results using meta-analysis was made. For selecting the best articles a three-step collection strategy was used, which resulted in a database of 38 publications. The review has shown that for measuring the quality of financial reporting researchers most frequently use models based on measurement of risk management, and the most common independent variables describing corporate governance are: the size of the audit committee, presence of independent directors on the supervisory board, dual role of CEO, proportion of independent directors in the audit committee, size of the supervisory board, proportion of accounting experts in the audit committee, and frequency of audit committee meetings